Gestión Académica enfocada desde la Calidad, de la Facultad de Ciencias Económicas y Administrativas de la Universidad Nacional de Itapúa – Paraguay (Journal on studies and research of academic knowledge, 2011)
The research work addresses the Academic Administration, Faculty of Economics and Administrative Sciences, National University of Itapúa, Paraguay, from the quality approach, describes its position, answering questions about the "doing" and from the "must do "management, recognizingthe principles of quality present in both academic and administrative management and the factors that influence the attainment of Quality.The level of research is exploratory and descriptive, phenomenological approach and multimodal or mixed. The study universe consists of principals, teachers, students, graduates and business executives. The instruments were applied to 42% of the population.The findings permit the inference that the institution is characterized by an organizational structure consistent with the needs, consistent in its internal functioning, with evidence of compliance with its purposes, mission and objectives. The administrative and financial procedures are appropriate medium according to the allocation, implementation and control the budget required to implement the Educational Project. These factors position the institution to a large extent on the quality parameters.According the research results, we propose an improvement p l an, wh i ch h i gh l i ghts the need for enhanced communication, training, upgrading, human resource focus, reviewing the budget to meet the development plan, implement mechanisms for monitoring, evaluation and development of the degree of fulfillment of educational projects and quality standards to ensure the permanence of the institution in the market and in time.
Keywords: management; quality; Academic Management; organizational structure; criteria for quality; improvement plan